Analisis Yuridis Pengolahan Data Fisik dan Yuridis Dalam Pendaftaran Tanah Menurut PP No 24 Tahun 1997 di Kantor Pertanahan Kabupaten Maros - Pransisto, Johamran (Jurnal Litigasi Amsir, 2023)
This study aims to identify and analyze legal studies on the Effectiveness of Processing Physical Data and Juridical Data According to PP. No. 24 of 1997 concerning Land Registration, and knowing and analyzing the factors that influence the management of physical data and juridical data in the registration of land rights according to PP. No. 24 of 1997 concerning Land Registration, to prevent state administration disputes from arising at the Maros District Land Office. The type of research used is the type and descriptive research approach. The results of the study show that the implementation of the management of physical data and juridical data in the registration of land rights to prevent the emergence of state administrative disputes at the Maros Regency Land Office is to realize legal certainty through the management of physical data and juridical data in the bookkeeping of rights in the registration of land rights and implementing concretely and being accountable for administration certainty and presenting information on registration of land rights has not been carried out effectively and efficiently. To realize the effectiveness of the management of physical data and juridical data according to PP. No. 24 of 1997 concerning land registration at the Maros District Land Office to prevent state administrative disputes from arising is influenced by several factors, namely legal substance; Legal structure; and legal culture